Representation of Nasionalism and Patriotism in The Song “Kami Nusa Hitam” - Saryono, David Mulyanto; Puspitasari, Maria (Technium Education and Humanities, 2024)
Abstract. Songs are cultural products with the power to influence and transform many individuals. Through the song "Kami Nusa Hitam," Rayen Pono and musicians from Eastern Indonesia promote a new identity known as Nusa Hitam, with a primary narrative focused on brotherhood, pride in local identity, and unity to foster nationalism and patriotism. Eastern Indonesia faces various social issues, including underdevelopment, poverty, and feelings of inferiority, which contribute to low self-esteem among its people. Additionally, stereotypes are frequently imposed on individuals from Eastern Indonesia. This study aims to elucidate the meaning of the lyrics of "Kami Nusa Hitam." The research methodology employed is Ferdinand de Saussure's semiotic analysis technique, which seeks to uncover representations of nationalism and patriotism within the text and lyrics. The analysis indicates that "Kami Nusa Hitam" embodies a profound message of nationalism and patriotism, rooted in pride and affection for local cultural identity. Furthermore, the song conveys that a robust local culture can serve as a fundamental factor in achieving national resilience, both on an individual level and in terms of the cultural resilience of the nation. Keywords: Nationalism, Patriotism, Popular Song, Cultural Resilience